Emerging treatment options for early mycosis fungoides - Fernández Guarino, Montserrat (My University, 2013)
: Mycosis fungoides is a candidate for skin-directed therapies in its initial stages. In recent years, therapeutic options outside of the normal treatment recommendations such as topical imiquimod, topical tazarotene, topical methotrexate, excimer light sources, and photodynamic therapy have been published with variable results. These alternatives have been useful in cases of localized mycosis fungoides that do not respond to routine treatments; nevertheless, more studies on these methods are still needed. This article summarizes the literature and data that are known so far about these treatments. Keywords: mycosis fungoides, topical treatments, excimer light, photodynamic therapy